The authentic assessment of educational actions: backward design and promotion of life skills - Vincenzo Nunzio Scalcione (Firenze University Press, 2022)
The processes of change that affect today's training system require a planning commitment aimed at finding flexible and, at the same time, effective answers. A training approach, oriented towards design models capable of proceeding with the assessment of performance, appears to be the element that defines authentic assessment. According to the methods of intervention estimated by Grant Wiggins and Jay McTighe, a methodology is proposed that starts from some assessment choices, intervening on the definition of the same methods of didactic planning, according to the tool of understanding by Design. The aim is to promote a lasting understanding, acquire skills for life, achieve the so-called promotion of an authentic assessment, a perspective within which the assessment aims to involve the student through real-life tasks. In the present discussion we have therefore proceeded to define the intervention framework of such an approach, proposing the examination of the theoretical references and design models, within a design intervention carried out in the school.   La valutazione autentica delle azioni educative: progettazione a ritroso e promozione delle competenze per la vita. I processi di cambiamento che investono il sistema formativo odierno necessitano di un impegno progettuale finalizzato alla ricerca di risposte flessibili ed, al contempo, efficaci. Un approccio formativo, orientato verso modelli progettuali in grado di procedere all'accertamento delle prestazioni risulta essere l'elemento che definisce la valutazione autentica. Secondo le modalità di intervento preventivate da Grant Wiggins e Jay McTighe, viene proposta una metodologia che muove da alcune scelte valutative, intervenendo sulla definizione delle stesse modalità della progettazione didattica, secondo lo strumento dell'understanding by Design. Il fine risulta quello di promuovere una comprensione durevole, acquisire competenze per la vita, conseguire la cosiddetta promozione di un authentic assessment, una prospettiva, all'interno della quale, la valutazione mira a coinvolgere l'alunno attraverso compiti di realtà. Nella presente trattazione si è quindi proceduto a definire il quadro di intervento di un simile approccio, proponendo la disamina dei riferimenti teorici e dei modelli progettuali, all'interno di una attività didattica realizzata nella scuola.